Accelerated aging for evaluation of vigor in Brachiaria brizantha ‘Xaraés’ seeds - Ariadne Morbeck Santos Oliveira; Marcela Carlota Nery; Karina Guimarães Ribeiro; Adriana Souza Rocha; Priscila Torres Cunha (Journal of Seed Science, 2020)
Abstract: The aim of this study was to adjust the accelerated aging test to evaluate the physiological potential of seed lots of Brachiaria brizantha ‘Xaraés’, represented by four lots. Seeds were tested by traditional accelerated aging and with saturated NaCl solution in five aging periods: 0, 24, 48, 72 and 96 hours. The profile of the lots was determined by the following measures: moisture content, germination test, first germination count, germination speed index, initial stand, emergence, and emergence speed index. The accelerated aging test makes it possible to separate the lots by the method of saturated NaCl solution for 24 hours and it is appropriate for evaluation of seed physiological potential.